The Influence of Muslim Religiosity on Tax Compliance: The Role of Distributive Justice as Moderator - Fitri Mareta; Damayanti Damayanti; Depita Anggraini; Ulin Nuha Alfani (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the influence of perceived experience and perceived value on customer loyalty among Gojek users, with customer satisfaction as a mediating variable. Methodology/Approach: The study uses a quantitative approach with data collected from 210 respondents through an online questionnaire distributed via Google Forms. The sampling technique applied was purposive sampling, and data were analyzed using Structural Equation Modeling (SEM) with the AMOS program. Results/Findings: The findings reveal that perceived experience and perceived value both have positive and significant effects on customer satisfaction and customer loyalty. Moreover, customer satisfaction positively mediates the relationship between perceived experience and customer loyalty, as well as between perceived value and customer loyalty. Conclusions: Customer satisfaction plays a crucial mediating role in strengthening the link between perceived experience, perceived value, and customer loyalty. This indicates that experiential and value perceptions are key drivers in building long-term loyalty among online transportation users. Limitations: This study is limited by the number of respondents and variables, focusing only on perceived experience, perceived value, customer satisfaction, and customer loyalty. Contribution: The research provides managerial implications for online transportation service providers, particularly Gojek, by emphasizing the importance of enhancing customer experience and perceived value to increase satisfaction and loyalty.